Area variations in infant mortality 1975-7. Issue 1 (March 1982) - Bradshaw, J; Edwards, H; Lawton, D; Staden, F; Weale, J; Weekes, A
Abstract : Infant mortality rates vary from area to area. Part of this variation is due to the socioeconomic characteristics of the area and part to other factors including the obstetric, paediatric, and community health services. Four social indicators associated with infant deaths are used to control for some of the variations in socioeconomic characteristics and residual variation is then examined. The four social indicators are the level of unemployment, the proportion of large families, the proportion of lone-parent families, and the level of overcrowding.